2007
DOI: 10.1038/sj.gt.3302964
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous cellular uptake of exogenous messenger RNA in vivo is nucleic acid-specific, saturable and ion dependent

Abstract: The development of new treatments in the post-genomic era requires methods for safe delivery of foreign genetic information in vivo. As a transient, natural and controllable alternative to recombinant viruses or plasmid DNA (pDNA), purified or in vitro transcribed messenger RNA (mRNA) can be used for the expression of any therapeutic protein in vitro and in vivo. As it has been shown previously, the simple injection of naked mRNA results in local uptake and expression. We show here that this process, in the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
165
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(177 citation statements)
references
References 17 publications
2
165
2
1
Order By: Relevance
“…The only study that investigated the uptake of RNA in vivo proposed a saturable Ca +2 ion-dependent process without defining the exact mechanism and cell type. 22 Similarly, for other naked nucleic acid based compounds, there is a lack of knowledge on mechanisms of internalization by APCs. For siRNA only uptake by metazoan cells has been studied, 23 whereas for plasmid DNA circumstantial evidence supports the hypothesis of uptake into macrophages via scavenger receptor A.…”
Section: Discussionmentioning
confidence: 99%
“…The only study that investigated the uptake of RNA in vivo proposed a saturable Ca +2 ion-dependent process without defining the exact mechanism and cell type. 22 Similarly, for other naked nucleic acid based compounds, there is a lack of knowledge on mechanisms of internalization by APCs. For siRNA only uptake by metazoan cells has been studied, 23 whereas for plasmid DNA circumstantial evidence supports the hypothesis of uptake into macrophages via scavenger receptor A.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was reported that transfection on intradermal injection of messenger RNA is saturated at a concentration of 0.05 mg=ml. This suggests a different uptake mechanism between intradermal mRNA injection and the tattooing of double-stranded DNA (Probst et al, 2007).…”
Section: Van Den Berg Et Almentioning
confidence: 99%
“…4,5 Preclinical experiments and human clinical trials testing administration of autologous DCs loaded in vitro with RNA as well as direct injection of RNA via different routes to reach DCs in situ showed feasibility, lack of toxicity and induction of the expected antigen-specific immune response. [6][7][8][9][10][11] Improvement of immunobioavailability of RNA-based vaccines in DCs has been a recurrent subject of our research, because the dose of the antigen may be one of the critical factors for generating strong and sustained antigen-specific immune responses. 12 In previous work, we have developed plasmid templates for in vitro transcription of RNA-encoded antigen with modified 3 0 structures (3 0 UTR and poly(A)tail) stabilizing the RNA and optimizing its translational performance.…”
Section: Introductionmentioning
confidence: 99%
“…15 This cap has important roles in all aspects of mRNA metabolism such as specific recognition of mature mRNA by the translational initiation factor eIF4E for formation of the 48S complex, translation initiation and stability of the RNA in the process of protein synthesis. 16 Capping of recombinant antigen-encoding RNA manufactured for preclinical development and clinical use is achieved by transcribing the DNA template with a bacteriophage RNA polymerase in the presence of all four nucleotide triphosphates and the cap dinucleotide m 7 GpppG as structural homolog of the endogenous cap structure. 3 However, not all of the RNA is capped, because the cap dinucleotide has to compete with guanosine triphosphate (GTP) for the initiation of transcription.…”
Section: Introductionmentioning
confidence: 99%